Compensation System in the Public Insurance Fund of Natural Disasters - Ali Ghesmati Tabrizi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2021)
Damages caused by natural disasters, which were formerly considered the result of the force majeure and were irreparable, are now compensable with the help of special legal systems. In addition to compensating the victims, these systems seek to prevent and reduce the effects of natural disasters in order to better manage the unpleasant effects of these Calamities. The Law on the «Establishment of the Public Insurance Fund of Natural Disasters» is an attempt to respond to public demand for security by the combination of compulsory insurance and governmental support to compensate for natural disasters. Nevertheless, it seems because of the long approval process and disregarding of the legal principles and practical experience of other countries, the legislature has failed to achieve its goals. The disordered basis, inadequate compensation, incomplete coverage, inattention to necessary financial resources, and the neglecting of preventive duties, in addition to not satisfying the victims, do not reduce governmental charges either. In this article, in addition to critical reviews of the Public Insurance an alternative solution to maintaining the insurance framework has been proposed to maintain the supervisory and supportive role of the government and effectively compensate for the adverse effects of natural disasters with the help of national solidarity.